88.6k views
3 votes
Indicate the general rule for the arithmetic sequence with a3 = -12 and a8 = -37.

an = -2 + (n-1)(-5)
an = -2 + (n-1)(5)
an = 2 + (n-1)(-5)
an = 2 + (n-1)(5)

User Overnet
by
5.9k points

2 Answers

3 votes

Answer:

the correct answer is an = -2 + (n-1)(-5). option A

User Adonike
by
5.7k points
7 votes

Answer:

Option A is correct

General rule for arithmetic sequence with
a_3 = -12 and
a_8 = -37 is;
a_n=-2+(n-1)(-5)

Explanation:

Arithmetic sequence states that a sequence where the difference between each successive pair of terms is the same.

The general rule for the arithmetic sequence is given by;


a_n=a+(n-1)d where

a represents the first term

d represents the common difference and

n represents the number of terms.

Given:
a_3 = -12 and
a_8 = -37


a_3 = -12

a+(3-1)d = -12 [Using arithmetic sequence rule]

a + 2d = -12

or we can write this as;

a = -12 - 2d ......[1]

Similarly, for
a_8 = -37 we have;


a+(8-1)d = -37

a+7d = -37 ......[2]

Substitute equation [1] into [2] to solve for d;

-12 - 2d +7d = -37

Combine like terms;

-12 + 5d = -37

Add both sides 12 we get;

-12 + 5d + 12 = -37 + 12

Simplify:

5d = -25

Divide both sides by 5 we get;

d = -5

Substitute the value of d in equation [1] to solve for a;

a = -2(-5) - 12

a = 10 -12 = -2

a = -2

therefore, the general rule for the arithmetic sequence with
a_3 = -12 and
a_8 = -37 is,
a_n=-2+(n-1)(-5)


User Slickelito
by
5.8k points